College students' binge drinking factors : Exploring factors affecting alcohol consumption through the theory of planned behavior - Willems, Jenna (My University, 2014)
Binge drinking, a form of excessive alcohol consumption, is a behavior most common among college students worldwide. Past research has shown this practice to have many negative consequences as well as changing fads and trends. Objective. The purpose of this study was to assess the individual and environmental characteristics that affect excessive alcohol consumption behaviors and trends through the framework of the Theory of Planned Behavior. Participants. A total of 445 undergraduate students from the University of Wisconsin-La Crosse participated in the study in March-April of 2014. Participants completed surveys consisting of demographic items as well as items related to alcohol consumption, Theory of Planned Behavior constructs, self-efficacy, and social belonging. Methods. Data were analyzed using logistic regression and analysis of variance. Results. Results indicated a significant correlation between binge drinking and subjective norm, positive attitude, self-efficacy, and behavioral intention to binge drink. Conclusions. Future binge drinking interventions should target 21-22-year-old college students through strategies related to changing perceptions regarding social approval and expectations, attitudes toward binge drinking, and intentions to binge drink.
Keywords: College students; Public health; Binge drinking